A Study on Leadership Qualities of Supervisory Officers (Divisional / Institution Heads) in ICAR Institutes (Indian Journal of Extension Education, 2014)
Leadership is the role and status of one or more individuals in the structure and functioning of group organizations which enable & to meet a need or purpose, through co-operation of the group members. The ICAR is an apex body with a multitude of research institutes under its realm. The organization is manned by scientific staff of different cadres, prescribed by hierarchical set-up. The leadership qualities of the immediate supervisors have a direct bearing on the productivity of the scientists in succession, which in turn determine the efficiency of technology flow and its transfer to the client system in the field. The present study was undertaken to assess the leadership qualities of supervisory level officers in the hierarchy. More than half of respondents (53.63 %) opined that the immediate supervisors possessed professional knowledge and expertise only to some extent, while 65.22 % said that the level of planning was largely top down, implying a bureaucratic approach. About 42.02 % said that considerable scope was given by superiors to act independently and 56.52 % reported of motivating the staff substantially to achieve higher level of performance. Ademocratic leadership, involving a bottom-up approach must be fostered within the limits of official hierarchy to enable the individuals in the organization to show case their skills and ability for enhancing the productivity of the organization.